2017
DOI: 10.1080/07420528.2017.1415922
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart-specific disruption of the circadian clock on systemic glucose metabolism in mice

Abstract: The daily rhythm of glucose metabolism is governed by the circadian clock, which consists of cell-autonomous clock machineries residing in nearly every tissue in the body. Disruption of these clock machineries either environmentally or genetically induces the dysregulation of glucose metabolism. Although the roles of clock machineries in the regulation of glucose metabolism have been uncovered in major metabolic tissues, such as the pancreas, liver, and skeletal muscle, it remains unknown whether clock functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Then, there is a negative feedback mechanism where an increase of PER/CRY complexes, in turn, inhibits the activity of BMAL1/CLOCK complexes [4]. Numerous in vivo and in vitro studies have shown that glucose has a significant effect on regulating biological clock signals [24], and hyperglycemia has influenced circadian rhythm on SCN and other specific peripheral tissues in vivo and in vitro [25,26]. The STZ-induced diabetic rat's BioMed Research International myocardium expresses circadian clock genes about 3 hours earlier than those of normal rats on a free diet [27].…”
Section: Discussionmentioning
confidence: 99%
“…Then, there is a negative feedback mechanism where an increase of PER/CRY complexes, in turn, inhibits the activity of BMAL1/CLOCK complexes [4]. Numerous in vivo and in vitro studies have shown that glucose has a significant effect on regulating biological clock signals [24], and hyperglycemia has influenced circadian rhythm on SCN and other specific peripheral tissues in vivo and in vitro [25,26]. The STZ-induced diabetic rat's BioMed Research International myocardium expresses circadian clock genes about 3 hours earlier than those of normal rats on a free diet [27].…”
Section: Discussionmentioning
confidence: 99%
“…LV diastolic posterior wall thickness (LVPWd), LV systolic posterior wall thickness (LVPWs), LV diastolic internal dimension (LVIDd), and LV systolic internal dimension (LVIDs) were measured from LV cross-sectional area. LV fractional shortening (FS%) was calculated using the formula, (LVIDd − LVIDs)/LVIDd × 100, as previously described [36].…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA of ventricular heart tissue was extracted with TRIzol RNA Isolation Reagents (Thermo Fisher Scientific Inc., Waltham, MA, USA). First-strand complementary DNA (cDNA) was synthesized using 250 ng of cDNA and the High-Capacity cDNA Reverse Transcription Kit (Thermo Fisher Scientific Inc. Real-time PCR was performed with 1× SYBR Premix Ex Tap II using a TP850 Thermal Cycle Dice Real-Time System (Takara Bio, Inc., Kusatsu, Japan), as previously described [36]. To analyze gene expression levels, the comparative Cycle threshold (CT) method was used, in which expression levels of target genes relative to Glyceraldehyde-3-phosphate dehydrogenase (Gapdh) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Adipose-specific Bmal1 -/- knockout mice show increased weight gain and adipose tissue mass, which might be due to increased food consumption during the daytime hours. Heart-specific Bmal1 -/- knockout mice show decreased heart function, systemic insulin resistance and decreased insulin-induced AKT phosphorylation in the liver (Nakao et al, 2018). By contrast, global and liver-specific Bmal1 -/- knockout and APOE -/- knockout mice show increased hyperlipidemia and atherosclerosis.…”
Section: Circadian Clock Genes and Metabolism In The Setting Of Nafldmentioning
confidence: 99%